Model Kemitraan untuk Mendorong Pengembangan Gandum di Indonesia: Kajian Literatur Sistematik - Cahyana, Octavian Bintang Shahab; Jayaprawira, Jefanya Diva Adriana; Kurniawan, Avra Sendi; Zebua, Damara Dinda Nirmalasari; Ningrum, Priskilah Febi Widya; Sheliena, Esther (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Wheat development in Indonesia continues to face various technical and non-technical challenges, including agroecological constraints, low farmer interest, limited access to capital, and market uncertainty. These conditions highlight the importance of strong institutional support through multi-stakeholder partnership models. This study aims to analyze partnership models, key actors involved, their strategic roles, and their relationship with farmers’ interest in developing wheat cultivation in Indonesia. The research employs a Systematic Literature Review (SLR) method by examining peer-reviewed articles indexed in Scopus published between 2010 and 2025. The literature selection process followed systematic stages, including identification, screening, eligibility assessment, and in-depth analysis of relevant studies. The findings reveal that successful wheat development requires integrated partnership models involving farmers, government agencies, processing industries, financial institutions, research institutes, universities, and cooperatives. Partnerships play a crucial role in technology provision, capacity building, access to finance, market assurance, risk management, and environmental sustainability. Furthermore, partnerships that provide price certainty, technology transfer, and institutional support are shown to enhance farmers’ motivation and participation in wheat cultivation. This study concludes that a coordinated and sustainable multi-actor partnership model is a key prerequisite for promoting national wheat development and reducing dependence on wheat imports.